Role of Medical Education in Pandemic Preparedness - Saurabh R Shrivastava; Prateek S Shrivastava; Ahishek Joshi (Medsci Publications, 2024)
Every pandemic that has been reported to date has impacted different domains of human life and civilization. The training imparted to medical students during their medical education is expected to enhance their competence and deal with the potential challenges that every pandemic places on human mankind. Medical education is expected to influence our pandemic preparedness in a multiple number of ways and it becomes our responsibility to expose medical students to different aspects during their training period in an incremental manner. Considering the wide extent to which pandemics can account for the loss of lives, human suffering, impairment of different sectors, and the potential that medical education can bridge the existing gap, there is an immense need to integrate topics pertaining to the pandemic and their preparedness in the medical curriculum. In conclusion, there is an immense need to ensure pandemic preparedness in medical education to produce resilient and adaptable health professionals. The need of the hour is to adopt a curriculum that has components of pandemic-related topics in a structured and systematic manner. This calls for the need to adopt a flexible curriculum and expose students to a structured training program, and effective communication skills.